A macroeconomic model with a financial sector - Markus K. Brunnermeier; Yuliy Sannikov (National Bank of Belgium, 2012)
This paper studies the full equilibrium dynamics of an economy with financial frictions. Due to highly non-linear amplification effects, the economy is prone to instability and occasionally enters volatile episodes. Risk is endogenous and asset price correlations are high in down turns. In an environment of low exogenous risk experts assume higher leverage making the system more prone to systemic volatility spikes - a volatility paradox. Securitization and derivatives contracts leads to better sharing of exogenous risk but to higher endogenous systemic risk. Financial experts may impose a negative externality on each other and the economy by not maintaining adequate capital cushion.
Keywords: 330; Finanzkrise; Volatilität; Verbriefung; Systemrisiko